Background study of NaI(Tl) crystals for the KIMS-NaI experiment. Issue 4 (May 2016) - Adhikari, P; Adhikari, G; Choi, S; Ha, C; Hahn, I S; Jeon, EJ; Joo, H W; Kang, W G; Kim, H J; Kim, H O; Kim, K W; Kim, N Y; et al.
Abstract: The DAMA experiment has reported an annual-modulation signal in an array of low-background NaI(Tl) scintillating crystals that may be caused by WIMP-nucleon interactions. However, to date there has been no direct confirmation of this result that uses the same taget nuclides. The Korea Invisible Mass Search (KIMS) collaboration has been engaged in an extensive R&D program to grow ultra-low background NaI(Tl) crystals for use as a direct test of the DAMA result using same nuclide targets. Six crystals were grown from different powders in order to understand mechanisms of internal background contaminations and to reduce their effects. Studies of internal backgrounds in these crystals were performed with the ultimate goal of reducing internal background contamination levels to 1 dru at 2 keV.